2020
DOI: 10.1101/2020.02.07.938860
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell mutational profiling delineates clonal trajectories in myeloid malignancies

Abstract: 1Myeloid malignancies, including acute myeloid leukemia (AML), arise from the proliferation and 2 expansion of hematopoietic stem and progenitor cells which acquire somatic mutations. Bulk 3 molecular profiling studies on patient samples have suggested that somatic mutations are obtained 4 in a step-wise fashion, where mutant genes with high variant allele frequencies (VAFs) are 5 proposed to occur early in disease development and mutations with lower VAFs are thought to be 6 acquired later in disease progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Recent studies have interrogated the clonal architecture of AML over time (45), and shown that somatic mutations may precede diagnosis of AML by months or years (46) and that deep sequencing of mutations can be used to differentiate age-related clonal hematopoiesis from pre-AML and predict AML risk in otherwise healthy individuals (47). Our approach detects system-wide perturbation before any leukemic blasts are seen in the blood, or differential expression of known leukemogenic marker genes, suggesting the signal detected by bulk RNA-seq is not driven solely by the presence of leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have interrogated the clonal architecture of AML over time (45), and shown that somatic mutations may precede diagnosis of AML by months or years (46) and that deep sequencing of mutations can be used to differentiate age-related clonal hematopoiesis from pre-AML and predict AML risk in otherwise healthy individuals (47). Our approach detects system-wide perturbation before any leukemic blasts are seen in the blood, or differential expression of known leukemogenic marker genes, suggesting the signal detected by bulk RNA-seq is not driven solely by the presence of leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…mutational data to individual cells. 22,28,29 In this study, we used the Tapestri technology to dissect T-ALL heterogeneity at diagnosis and clonal evolution during chemotherapy treatment. Tapestri is amplicon based, and we designed a panel to interrogate 305 genomic regions that are frequently mutated in ALL.…”
Section: Clonal Evolution During Treatment and At Relapsementioning
confidence: 99%
“…Moreover, although DNA bulk sequencing can greatly inform cancer biology, it cannot distinguish which mutations occur in the same clone(s) as well as it cannot measure in deep clonal complexity. Single-cell DNA sequencing (sc-DNAseq) could overcome this issue, especially if associated to sc-RNAseq: preliminary and unpublished evidences in acute myeloid leukemia [67] suggest that scDNA-seq could precisely map the clonal trajectory of each patient, identifying the specific mutation combination that synergize to promote clonal expansion and dominance. Therefore, a combination of single cell genomic and transcriptomic tools applied to pancreatic cancer is highly desirable, and probably the only way to reveal the complete PDAC sub-clonal structure.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%